Thermostable amperometric lactate biosensor with Clostridium thermocellum L-LDH for the measurement of blood lactate - Özkan, Melek; Erhan, Elif; Terzi, Ozlem; Tan, Ibrahim; Ozoner, Seyda Korkut (Elsevier, 2009)
The gene for Clostridium thermocellum L-lactate dehydrogenase enzyme was cloned into pGEX-4T-2 purification vector to supply a source for a thermostable enzyme in order to produce a stable lactate biosensor working at relatively high temperatures. The purified thermostable enzyme (t-LDH) was then immobilized on a gold electrode via polymerization of polygluteraldehyde and pyrrol resulting in a conductive co-polymer. t-LDH working electrode (t-LDHE) was used for determination of lactate in CHES buffer. Amperometric response of the produced electrodes was measured as a function of lactate concentration, at a fixed bias voltage of 200mV in a three-electrode system. The linear range and sensitivity of the biosensor was investigated at various temperatures in the range of 25-60 degrees C. The sensitivity t-LDHE increased with increasing the temperature and reached its highest value at 60 degrees C. The calculated value was nearly 70 times higher as compared to the sensitivity value of the same electrode tested at 25 degrees C. The sensing parameters of t-LDHE were compared with the electrodes produced by commercially available rabbit muscle LDH (m-LDH). The sensitivity of t-LDHE was nearly 8 times higher than that of m-LDHE. t-LDHE was found to retain its activity for a week incubation at refrigerator (+5 degrees C), while m-LDHE lost its activity in this period. t-LDHE was also tested in the presence of human blood serum. The results showed that the current increased with increasing concentrations of lactate in the human blood serum and the biosensor is more sensitive to serum lactate as well as the commercial lactate dissolved in serum as compared to the commercial lactate dissolved in CHES buffer. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Amperometric lactate biosensors; Cloned LDH; Conductive polymers; Thermostable LDH